Decoding oncogenic secrets of regulator of chromosome condensation 1: A breakthrough mechanistic evidence from breast and lung cancer models. - Mohamed El-Tanani; Shakta Mani Satyam; Syed Arman Rabbani; Razan M Obeidat; Yahia El-Tanani; Alaa A A Aljabali; Taher Hatahet (PLoS ONE)
The Regulator of Chromosome Condensation 1 (RCC1), a master regulator of cell cycle progression, chromatin structure, and nuclear transport, emerges as a powerful driver of cancer progression. Elevated RCC1 expression in breast and lung cancers is closely tied to enhanced tumor cell survival, proliferation, and metastasis, positioning it as a promising therapeutic target. This study unveils RCC1's pivotal role in cancer biology by silencing its expression in MDA-MB-231 (breast cancer) and A549 (lung cancer) cell lines using shRNA. RCC1 knockdown dramatically reduced cell viability, colony formation, and motility, while inducing apoptosis, as evidenced by increased apoptotic markers and reduced anti-apoptotic Bcl2 expression. Gene expression analysis revealed downregulation of cell cycle and DNA repair pathways, highlighting RCC1's critical role in sustaining oncogenic mechanisms. These findings underscore RCC1 as a gatekeeper of tumor survival, capable of resisting apoptosis and promoting metastasis. Targeting RCC1 offers a dual advantage: disrupting cancer growth and enhancing apoptotic pathways, creating an exciting opportunity for precision therapies. By illuminating RCC1's integration into survival networks, this study not only advances our understanding of cancer biology but also lays the groundwork for innovative treatments aimed at halting cancer progression and metastasis.